INOVASI LITERASI GURU MELALUI MEDIA BACA DAN TULIS PADA GURU BUSTANUL ATHFAL DI KALIKOTES KLATEN - Winarti, Ambar; Sulistyowati, Arlina Dhian; Hastuti, Retno Yuli (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this activity is a partner who is the Head of the Aisyiah Asociation Bustanul Athfal Kalikotes District, namely Aisyiah Asociation Bustanul Athfal Kindergarten. The success of early childhood education lies with the educator or teacher. Educators or teachers must be able to guide, assist and direct their students. One of them is optimizing the mother’s tanguage, namely reading and writing, so that the ability of children in other fields can be mastered towards further education. Literacy development carried out by PIAUD teachers is to create, compiled and develop materials, media strategies and activities in teaching materials that will later be applied or applied in the learning process in the classroom in accordance with the level of early childhood. One of these alternatives aims to develop the creativity innovation of teachers in managing the content of writing and reading teaching materials that are appropriate for the PIAUD program at Aisyiah Asocioation Bustanul Athfal Kalikotes District Kindergarten. It is important for innovation and creative teachers